Protective effects of allopurinol against acute liver damage and cirrhosis induced by carbon tetrachloride: Modulation of NF-κB, cytokine production and oxidative stress - Aldaba-Muruato, Liseth R.; Moreno, Mario G.; Shibayama, Mineko; Tsutsumi, Víctor; Muriel, Pablo (Biochimica et biophysica acta, 2012)
The aim of this work was to evaluate the hepatoprotective ability of allopurinol to prevent the liver injury induced by carbon tetrachloride (CCl 4). Acute liver damage was induced with CCl 4 (4 g/kg, by gavage); allopurinol (50 mg/kg, by gavage) was given 1 h before and 1 h after CCl 4 intoxication and two daily doses for the previous three days. Cirrhosis was established by CCl 4 administration (0.4 g/kg, i. p. three times a week, eight weeks); allopurinol was administered (100 mg/kg, by gavage, daily) during the long-term of CCl 4 treatment. Alanine aminotransferase (ALT), γ-glutamyl transpeptidase (γ-GTP), xanthine oxidase (XO), lipid peroxidation, reduced and oxidized glutathione (GSH, GSSG, respectively), hydroxyproline and histopathologycal analysis were performed. Nuclear factor-κB (NF-κB), pro-inflammatory and anti-inflammatory cytokines, transforming growth factor-β (TGF-β) and metalloproteinase-13 (MMP-13) were analyzed by Western blots. Acute injury increased ALT and γ-GTP activities, additionally enhanced NF-κB nuclear translocation and cytokines production such as tumor necrosis factor-α, interleukine-1β, and interleukine-6. Allopurinol partially prevented these effects, while increased interleukine-10. Acute and chronic CCl 4 treatments altered the levels of XO activity, lipid peroxidation, and GSH/GSSG ratio, while these remained within normal range with allopurinol administration. Necrosis, fibrosis and TGF-β production induced in chronic injury were partially prevented by allopurinol, interestingly, this drug induced MMP-13 activity. Allopurinol possesses antioxidant, anti-inflammatory and antifibrotic properties, probably by its capacity to reduce NF-κB nuclear translocation and TGF-β expression, as well as to induce MMP-13. General significance Allopurinol might be effective treatment of liver diseases. ► Allopurinol protects against necrosis regardless of dose and exposure time with CCl 4. ► Allopurinol maintained redox balance both hydrophilic and lipophilic induced by CCl 4. ► Allopurinol inhibited partially the nuclear translocation of NF-κB. ► Allopurinol showed immunomodulatory effects on pro- and anti-inflammatory cytokines. ► Allopurinol reduces fibrosis by decreased TGF-β expression couple induce MMP-13.